Economic insecurity and fertility intentions: the case of Italy - Francesca Modena; Concetta Rondinelli; Fabio Sabatini (Economics and Econometrics Research Institute (EERI), 2012)
We aim to provide an explanation for the combination of the relatively low female participation rates and lowest-low fertility levels in Italy. Starting from the assumption that childbearing decisions also depend on uncertainty about future employment, income, and wealth, we empirically assess how fertility intentions are affected by: 1) the deprivation of a quality job, which may severely compromise the employability of workers and is likely to provoke feelings of insecurity about future employment; 2) conditions of economic disadvantage in terms of household income and wealth, which may imply insufficient means to deal with potential adverse future events, thereby generating in the household feelings of anxiety and economic insecurity. We show that the instability of women's work status (i.e. the holding of occasional and precarious employment positions) significantly discourages the decision to have a first child. Low levels of household wealth significantly and positively influence the decision to postpone, or even decide against, having a first child. The chances of further childbirth are significantly and negatively influenced by household income insecurity.
Keywords: C25; J13; 330; Economic insecurity; income; wealth; fertility; childbearing; employment instability; precarious employment; Italy